EFEKTIVITAS KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN PROJECT BASED LEARNING BERBANTUAN MEDIA VIDEO SISWA KELAS IX SMP NEGERI 1 PADANG PANJANG - Fauzaturrahmi; Farel Olva Zuve (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to describe the effectiveness of descriptive text writing skills using Project Based Learning assisted by video media in class IX students of SMP Negeri 1 Padang Panjang. The method used in this research is an experiment with a post-test only control group design. The research results show that the skill of writing descriptive text using Project Based Learning assisted by video media is more effective than conventional methods. The average score of students who used this method was in the very good category, while those who did not use this method were in the fair category. Thus, this learning model is recommended to improve the quality of learning to write descriptive texts in schools.